Liquidity Shocks and Stock Market Reactions - Turan G. Bali; Lin Peng; Yannan Shen; Yi Tang (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
This paper investigates how the stock market reacts to firm level liquidity shocks. We find that negative and persistent liquidity shocks not only lead to lower contemporaneous returns, but also predict negative returns for up to six months in the future. Long-short portfolios sorted on past liquidity shocks generate a raw and risk-adjusted return of more than 1% per month. This economically and statistically significant relation is robust across alternative measures of liquidity shocks, different sample periods, and after controlling for various risk factors and firm characteristics. Furthermore, the documented effect is stronger for small stocks, stocks with low analyst coverage and institutional holdings, and for less liquid stocks. Our evidence suggests that the stock market underreacts to firm level liquidity shocks, and that this underreaction can be driven by investor inattention as well as illiquidity.
Keywords: G02; G10; G11; G12; G14; C13; 330; stock returns; liquidity shocks; stock market reactions; underreaction; investor attention